(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
the study dealt with the effect of some of the most important organizational factors affecting job satisfaction for employees at Tishreen University, where the study aimed to study the most important organizational factors affecting job satisfaction for employees at Tishreen University, which are factors related to human labor relations and wages. Tishreen University, relying on the statistical sample law, and the researcher relied on interviews and the questionnaire as a main source for data collection. A questionnaire was designed for the workers in the research sample, and the data was processed using the SPSS statistical analysis program version /20/ using the appropriate statistical indicators, Among the most important findings of the study is the existence of a moral relationship between human labor relations and job satisfaction for employees at Tishreen University, as there is job satisfaction resulting from human labor relations, and also the existence of a moral relationship between wages and job satisfaction for employees at Tishreen University, as there is no Job satisfaction resulting from wages. The most important recommendations recommended by the researcher were: that a wage system be developed in line with global and local changes and developments, and in line with living conditions, life requirements and harsh conditions, as well as supporting the Human Resources Management Department in educational institutions because of their effective role in providing human resources Qualified, the researcher also recommended paying attention to providing moral incentives to workers because of their positive impact on their performance.